2020
DOI: 10.1021/acs.jpca.0c10060
|View full text |Cite
|
Sign up to set email alerts
|

Competition between a Tetrel and Halogen Bond to a Common Lewis Acid

Abstract: The T and X atoms of TF3X (T = C, Si, Ge, Sn; X = Cl, Br, I) can engage in a tetrel or halogen bond, respectively, with an approaching NH3 base. With the exception of T = C, the tetrel bonds are considerably stronger than the halogen bond regardless of the nature of T or X. Because both bonds involve electron acceptance by the central TF3X Lewis acid, there is a negative cooperativity between these two bonds when both are present. The halogen bond is weakened much more than is the tetrel bond and is in fact co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 88 publications
0
18
1
Order By: Relevance
“…A great number of experimental and theoretical investigations involving TtBs [2,20,64,65] are concentrated on the lighter elements (carbon and silicon), while those studying the heavier tetrels are scarcer [66][67][68][69]. Nevertheless, two excellent reviews are available including several X-ray crystal structures that prove the ability of Ge, Sn to establish highly directional interactions [70,71], which are key for assembling the crystal packing of many germanium and tin derivatives.…”
Section: Germanium and Tinmentioning
confidence: 99%
“…A great number of experimental and theoretical investigations involving TtBs [2,20,64,65] are concentrated on the lighter elements (carbon and silicon), while those studying the heavier tetrels are scarcer [66][67][68][69]. Nevertheless, two excellent reviews are available including several X-ray crystal structures that prove the ability of Ge, Sn to establish highly directional interactions [70,71], which are key for assembling the crystal packing of many germanium and tin derivatives.…”
Section: Germanium and Tinmentioning
confidence: 99%
“…Mutual Weakening. An earlier work 56 had shown that the formation of a TB on one end of the T−X bond tended to severely weaken, and in many cases even eliminate, the possibility of a XB to the other end of this bond. This idea was tested here for the T−Z bond between a tetrel and pnicogen atom.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The earlier comparison 56 of a TB with a XB, again with both T and X atoms situated on the same covalent bond, had observed the TB to be much stronger than the XB, regardless of the nature of the T or X atoms, or what periodic table rows they were drawn from. This distinction was true even if the substituents on the T atom were changed from F to H. The only exception had been the cases with T = C, where a TB was questionable, with interaction energies on the order of only 1 kcal/mol.…”
Section: ■ Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the required distortion to a planar unit so as to form such π‐holes was also much more energetically costly. The Si··NH 3 σ‐hole tetrel bond interaction energy of SiF 3 SbF 2 is 37 kcal/mol 86 and that for SiF 3 Cl is 36 kcal/mol 87 …”
Section: Summary and Discussionmentioning
confidence: 99%